Application of major ion concentrations for the prediction of stable isotopic composition in surface water - Chen, Kai; Sun, Linhua (Journal of Environmental Engineering and Landscape Management, 2021)
The δ2H and δ18O values in water bodies are essential to the management of water resources because of the ability to insight into hydrological processes. In this study, we have measured and analyzed the major ions (Na+, K+, Ca2+, Mg2+, Cl–, SO24– and HCO–3 ) and stable H-O isotopes (δ2H and δ18O) for fifteen surface water samples collected from the Xinbian River in Suzhou, northern Anhui Province, China. The results show that all of the water samples are classified to be Na-HCO3 type, and the mean values of δ2H and δ18O are –42.93‰ and –5.36‰, respectively. Gibbs diagram and the relationship between δ2H and δ18O indicate that both water chemistry and stable isotopes in river water are mainly controlled by evaporation. Correlation analysis reveals that a significant correlation between major ions and δ18O. Predictors (K+, SO24– and HCO–3 ) have been selected by optimal subset regression analysis were used to model the δ18O values in the river water. Moreover, the residuals of the model were normally distributed and values between –0.2‰ to 0.2‰ for most water samples, suggesting a strong relationship between the observed and predicted δ18O values.